Corrigendum to "Haemodynamic impacts of myocardial bridge length: A congenital heart disease" [Comput. Methods Progr. Biomed., 175 (2019) 25-33]. (July 2019) - Javadzadegan, Ashkan; Moshfegh, Abouzar; Mohammadi, Maryam; Askarian, Mahsa; Mohammadi, Mahsa
Abstract: In this corrigendum, the authors would like to acknowledge the cardiac catheterization laboratory staff at Tehran Heart Center for their assistance in performing the studies under the ethics application TH38-02-2017-20.